Religious Harmony Forum (FKUB) Strategy in Increasing Religious Moderation Jurisprudence in Bengkulu Province - Khairiah Khairiah; Irsal Irsal; Nurahmah Putri (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
Religious moderation remains challenging for some individuals, evident in the rise of intolerance, radicalism, disputes, and societal conflicts stemming from diversity. This study aims to map and describe the strategies employed by Interfaith Harmony Forums (FKUB) in enhancing religious moderation. Utilizing a qualitative descriptive method, primary and secondary data were collected from FKUB institutions in various districts and provinces. Primary data included profiling, motivations, challenges faced, and solutions implemented by FKUB administrators and members in managing difficulties. The research findings indicate an improvement in religious moderation in Bengkulu Province, as FKUBs have implemented collaborative patterns with the community, conducted work programs, coordinated with religious and community leaders, promoted legal awareness, and engaged in monitoring activities. However, some FKUBs encounter difficulties due to a lack of dedicated secretariat offices, reliance on temporary status, inadequate facilities, and limited budget allocation, leading to reliance on personal funds for religious moderation activities. This study suggests further research exploring regional comparative aspects and employing diverse data and methods to address FKUBs' challenges in enhancing religious moderation